IMPLEMENTATION OF TEACHER AND STAFF ABSENCE SYSTEM AT ANDROID-BASED SCHOOLS - Fahmi Kurniawan; Zulham Sitorus (INFOKUM, 2022)
Attendance is part of an important role in every institution, especially in educational institutions. Where attendance is one of the main supports to support and motivate every activity in it. As is the case with the PAB 5 Kelambir Lima Vocational School, which is currently still using the manual method, namely by handwriting. This method is very vulnerable for an educational institution because the level of discipline cannot be controlled and can be misused by irresponsible people. For this reason, it is necessary to have a digitization-based attendance system that utilizes an Android smartphone. With the existence of a digitization-based attendance system, it can provide performance achievements at the school. The system that will be built later is that every employee and teacher, if they want to be absent, must use a smartphone by sending a photo and being absent 100 meters from the workplace. Then the principal will check the attendance of teachers and employees every month.